2021
DOI: 10.1002/ajb2.1685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant origin and phenological stage on the allelopathic activity of the invasive species Oxalis pes‐caprae

Abstract: PREMISE Invasion processes involve several mechanisms, some of which have received little attention. Allelopathy has been invoked as an invasion driver according to the novel weapon hypothesis (NWH), and polyploidization can also be an important factor for invasion success. However, very few studies have addressed both topics together. We analyzed the allelopathic effect of the polyploid Oxalis pes‐caprae, an invader in mediterranean‐climate areas worldwide, from different origins and ploidy levels (native: So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In natural communities, each species has the inherent ecological niche to achieve coexistence [35]. In our study, we found that O. articulata had the highest IV in control communities because, as an alien noninvasive species, it has strong stressful resistance and a strong allelopathic effect that inhibits the growth of native plants, which is beneficial to expanding the living space and achieving rapid growth [36,37]. The IV of A. philoxeroides was much higher than that of other accompanying species in the invaded communities, possibly due to its strong clonal reproductive ability and phenotypic plasticity, allowing this invader to plunder resources on a large scale, enhance competitiveness, and thus suppress native plants [22,24,38].…”
Section: Mechanism Of Impact Of Soil On Community Structure and Plant...mentioning
confidence: 76%
See 1 more Smart Citation
“…In natural communities, each species has the inherent ecological niche to achieve coexistence [35]. In our study, we found that O. articulata had the highest IV in control communities because, as an alien noninvasive species, it has strong stressful resistance and a strong allelopathic effect that inhibits the growth of native plants, which is beneficial to expanding the living space and achieving rapid growth [36,37]. The IV of A. philoxeroides was much higher than that of other accompanying species in the invaded communities, possibly due to its strong clonal reproductive ability and phenotypic plasticity, allowing this invader to plunder resources on a large scale, enhance competitiveness, and thus suppress native plants [22,24,38].…”
Section: Mechanism Of Impact Of Soil On Community Structure and Plant...mentioning
confidence: 76%
“…D. indica has a high nitrogen absorption rate, while N-NO 3 , as the main nitrogen source, can promote the lateral root growth of D. indica and participate in metabolic regulation [71,72]; thus, D. indica positively correlates with N-NO 3 . O. articulata has thick roots and mainly relies on bulb propagation, which prompts it to distribute in loose and porous soil environments with high ORG [36,37].…”
Section: Mechanism Of Impact Of Soil On Plant Species Distributionsmentioning
confidence: 99%
“…Also, a clear negative effect of AC on plant biomass and survival was also reported in a previous study (Yuan et al ., 2021). Although AC was proven to be valid in allelopathic studies by blocking allelopathic effects (e.g., Sturm et al ., 2018; Kheirabadi et al ., 2020; Lorenzo et al ., 2021), experimental designs as the one used in this study must allow the identification of possible isolated and interactive effects of AC on target plants. As AC may have species-specific effects on plant performance through changes in chemical and biological properties of soils, it is essential to account for these effects in allelopathy studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we used dried instead of fresh plant material because it is a useful way to conserve and store the surplus plant material before its use, preventing decomposition and keeping allelopathic potential (Bonanomi et al ., 2018; Gatto et al ., 2021). We also used activated carbon (AC), as an allelopathy neutralizer, commonly used to discriminate if the effects of plants are driven by allelopathic compounds (Sturm et al ., 2018; Lorenzo et al ., 2021). Moreover, as the use of U. europaeus materials is relevant in invaded areas, because there is already an enormous quantity of undesirable U. europaeus plants needed to be removed, the plants used in invaded areas need to be cut before seeding, and even before flowering, to avoid any possibility to spread seeds or add invasive seeds to the crop field, which could increase the invasion problem and affect the crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…in coastal areas [11], Robinia pseudoacacia L. and Ailanthus altissima (Mill.) Swingle in mixed forests [12], Oxalis pes-caprae L. in ruderal and agricultural lands [13,14], and Eichhornia crassipes (Mart.) Solms in water bodies and courses [15,16].…”
Section: Introductionmentioning
confidence: 99%